Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (STAD) terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VII SMP Negeri 3 Siborongborong Tahun Pembelajaran 2023/2024. - Eyen Septini Situmeang; Andar Gunawan Pasaribu; Ordekoria Saragih; Risden Anakampun; Tianggur Medi Napitupulu (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The research aims to find out how much influence the application of the Student Teams Achievement Divisions (STAD) type cooperative learning model has on the active learning of Christian Religious Education and Characteristics of class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence of the Student Teams Achievement (STAD) type cooperative learning model on the active learning of Christian Religious Education and Characteristics of class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year. Descriptive and inferential quantitative research methods. The population of all class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year who are Protestant Christians is 109 people. The sample was random (random sampling) namely 50% of the total population, namely 55 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.574>rtabel=0.226 and tcount=5.103>ttable=2.00575 shows that there is a positive and significant relationship between the Student Teams Achievement Divisions (STAD) type cooperative learning model and active learning in Christian Religious Education and student character. b) Regression equation. c) The determination test shows that the magnitude of the effect is 32.95%. d) Hypothesis testing obtained Fcount=25.751>Ftable=3.15 then H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the Student Teams Achievement Divisions (STAD) type cooperative learning model on the learning activity of Christian Religious Education and Characteristics for class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year.